Komposisi jenis dan kelimpahan fitoplankton perairan laut riau - Dewi Ariana; Joko Samiaji; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in April 2013 and was located at Riau marine waters. Samples were analyzed in the Biology Laboratory of Marine Science Department of Fisheries and Marine Science Faculty of Riau University. The aim of this study was to observe the phytoplankton communities. This research used survey method. The study found 31 species of phytoplankton, these were 19 species from Bacillariophyceae, 9 species from Dinophyceae, 2 species from Chlorophyceae and 1 species from Cyanophyceae. Phytoplankton was dominated by group of Bacillariophyceae (Diatoms) 61%. The other groups comprising of Dinophyceae 29%, Chlorophyceae (7%), and Cyanophyceae 3%. Phytoplankton abundance varied from 87-593 ind/L, the higest value in station 9 Zone III and the lowest value in station 11 zone III. Whereas the highest value of zone abundance was zone II 443 ind/L and the lowest was zone I 253 ind/L. Phytoplankton community was dominated by the group of diatoms, such as Nitzschia sigma, Thallasiothrix longissima, and Thallasiothrix delicatula.Keywords: Marine Phytoplankton, Bacillariophyceae, Marine of Riau